Slow relaxation of the magnetization observed in mononuclear Ln–radical compounds with D4d geometry configurations. Issue 2 (7th December 2018) - Chen, Peng Yun; Wu, Ming Ze; Liu, Zhong Yi; Tian, Li; Zhang, Yi Quan
Abstract : Three monometallic Ln-NIT complexes have been synthesized based on a pyrazole radical. The central Ln III ions are all in D 4d polyhedron configurations. Tb's complex shows a single relaxation process. Dy's complex exhibits complicated relaxation processes. Abstract : The combination of Ln III ions (Gd III, Tb III or Dy III ) and a pyrazole nitronyl nitroxide radical results in three isomorphous complexes, namely, [Ln(hfac)3 (NIT-Pyz)]2 (Ln = Gd(1 ), Tb(2 ), Dy(3 ); hfac = hexafluoroacetylacetone; NIT-Pyz = 2-{3-pyrazolyl}-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide). Single crystal X-ray diffraction studies revealed that all of them are composed of two crystallographically independent mononuclear systems, in which the central Ln III ions are coordinated by three hfac and one bidentate chelating NIT-Pyz radical. The central Ln III ions are all in square antiprism geometry ( D 4d ) polyhedron configurations. Based on the spin Hamiltonian calculations, there exist antiferromagnetic couplings in the Gd III -NIT radical system in complex1 . Complexes2 and3 show frequency-dependent out-of-phase signals in a zero field indicating single-molecule magnetic behavior. Moreover, Tb's complex (2 ) shows a single thermal relaxation process with an energy barrier of 26 K. For Dy's complex (3 ), the Orbach and Raman processes both contribute to the magnetic relaxation behaviors.